WP 4: Integrated food, land, water and energy systems for climate resilient landscapes - Baum, Michael; Lahham, Nisreen; Brouziyne, Youssef; Anarbekov, Oyture; Nangia, Vinay; Abay , Kibrom; Nasr-Allah, Ahmed; Lal Jat, Mangi (International Center for Agricultural Research in the Dry Areas, 2022)
From Fragility to Resilience in Central and West Asia and North Africa (F2R CWANA) WP 4: Integrated food, land, water, and energy systems for climate-resilient landscapes Inception Workshop Morocco May 17, 2022.